(untitled) (Architecture Image Studies, 2024)
A palimpsest is a reused manuscript where the original text has been erased to make room for new writing, but traces of the old text remain visible. Over time, the concept of palimpsest has been used in various fields, including literature, painting, and later architecture. Architectural palimpsest refers to the transformation of a building or space over time, reflecting the accumulation of different architectural layers. This term describes processes such as adding new structures to old ones or adaptively reusing existing buildings while preserving traces of the past. Industrial heritage includes structures and facilities from the Industrial Revolution, such as factories, warehouses, mines, gasometers, and gasworks. These buildings carry the industrial imprints of the past and hold historical, cultural, and economic significance. This study aims to emphasize the importance of the palimpsest concept in architecture through an analysis of adaptively reused industrial heritage. Following a literature review, the methodology involves a comparison of two similar examples of industrial heritage adaptive reuse: Vienna Gasometer and Hasanpaşa Gasworks, located in different countries. The analysis is conducted within the context of the palimpsest concept and adaptive reuse. As a result, the study concludes that industrial heritage buildings, which have lost their original function but hold a place in the collective memory and identity of their cities, should be adaptively reused in a way that reflects the traces of the era they belong to without damaging their heritage value. The study aims to contribute to future research in this field.